The Color Red Is Implicitly Associated With Social Status in the United Kingdom and China - Wu, Yin; Lu, Jingyi; van Dijk, Eric; Li, Hong; Schnall, Simone (Frontiers in Psychology, 2018)
Research and theorizing on human societies have shown that the color red plays a large role in human psychological functioning. The aim of the present study was to test the association between red and high-status symbols across cultural contexts. Using the Implicit Association Test (IAT) paradigm, across seven experiments (N = 357), we demonstrated that participants exhibited a faster association of red color and logos of high-status stimuli compared to red color and logos of low-status stimuli. The effect was shown among both males and females, with two different types of status symbols (car logos and university logos), and with four different contrast colors (white, gray, green, blue). Moreover, this association was observed in both United Kingdom and China. These findings provide compelling evidence for the implicit association between the color red and high social status across two different cultural contexts.